Makna Logo Kementerian Hukum Dan Ham RI : Analisis Semiotika Peirce - Rahman Djalun; Jamiati KN (Lembaga Pengembangan Kinerja Dosen, 2024)
Basically, the term semiotics comes from the Greek word Semeion which means sign. The sign itself can be interpreted as something on the basis of a previously created social agreement that can be considered to represent something else. Previously, a sign could be interpreted as something that referred to the existence of another thing. Semiotic analysis here is an attempt to do something with the aim of feeling the presence or existence of something strange and foreign, something that we need to question more deeply when we observe the surrounding environment, read a text or certain narrative/discourse, observe the signs around us. We. Semiotics is also a scientific study which basically aims to understand and understand the existence of signs in human life. This can be interpreted as meaning that we must give everything that is in human life a meaning because we can see things related to human life as signs that have a meaning that has its own philosophical nature.